Enhancing Community Resources of the Muhammadiyah Branch in Sidoarjo through Paralegal Training to Establish a Legal-Cadre Village - Shery Muis, Lidya; Budi Purwaningsih, Sri; Ridlo Phahlevy, Rifqi; Amanda, Filia; Restya Purlianasari, Fridayani (Borobudur Journal on Legal Services, 2025)
The village, as the smallest unit of governance within Indonesia’s governmental system, nonetheless holds a strategic role in realising justice for the community. The involvement of the Muhammadiyah Branch Association, as a community-based organisation at the village level, serves as a frontline force in addressing social issues within society, particularly legal problems faced by underprivileged citizens. The presence of legal cadres within the Muhammadiyah Branch Association is expected to provide legal assistance in resolving legal issues and offering solutions that can be addressed at the village level. One of the challenges faced is the limited number of human resources at the branch level with legal expertise. A viable solution to this problem is to enhance legal knowledge through Paralegal Training for Muhammadiyah branch cadres. Before engaging with the community, paralegals are equipped with both theoretical and practical legal knowledge to handle and resolve legal issues encountered by the public. Strengthening the competence of Muhammadiyah branch cadres as paralegals is expected to optimally support village governments in addressing and solving legal challenges at the village level. In the future, paralegals are envisioned to become agents of change in the realisation of legally empowered villages.